Cigarette smoke extract induces p38-mediated expression and ROS/rho-mediated translocation of alpha 2C adrenoceptor in human microvascular smooth muscle cells - Manal M. Fardoun (22303813) (2025)
Raynaud's phenomenon (RP) is a vascular disease characterized by exaggerated vasoconstriction in response to stressors, mainly cold and emotional stress. This vasoconstriction is mediated solely by alpha 2C-adrenoceptors (α2C-AR) expressed in vascular smooth muscle cells of dermal arterioles. Several factors, among which is cigarette smoking, are associated with aggravated symptoms of and increased risk for RP. Evidence shows that cigarette smoking induces the production of reactive oxygen species (ROS), which is a major driver of RP pathogenesis. However, the exact mechanism by which smoking contributes to RP or α2C-AR remains unclear. Here, we show that cigarette smoke extract (CSE) upregulates the expression of α2C-AR in a concentration- and time-dependent manner in VSMCs extracted from human dermal arterioles. This increase is associated with the activation of p38 MAPK, as pretreatment with SB-202190, a p38 specific inhibitor, attenuated CSE-induced α2C-AR expression. Furthermore, our results show that CSE induces ROS production followed by increased RhoA activation. We also show that CSE induces translocation of vascular α2C-AR to the plasma membrane, and that this mobilization is attenuated by inhibiting ROS via N-acetylcysteine or apocynin. Similarly, inhibition of Rho kinase via H- 11522 abolished CSE-induced α2C-AR translocation. Collectively, these results indicate that CSE activates two different signaling pathways to induce the expression and the translocation of α2C-AR. While CSE activates a p38-dependent mechanism to increase α2CAR expression, it initiates the receptor's spatial and functional rescue via a ROS/RhoA signaling pathway. These results provide mechanistic insight into the effect of cigarette smoking on RP, and further reinforce that smoking avoidance/cessation is critical to manage this disease, especially in the absence of a definitive drug for RP. Other Information Published in: Progress in Cardiovascular Diseases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.pcad.2025.01.002